Who defines urban regeneration? Comparative analysis of medium-sized cities in Poland and Russia - Ciesiółka, Przemysław. Autor; Gunko, Maria. Autor; Pivovar, Galina. Autor (IGiPZ PAN, 2020)
The aim of the current study was to identify the main actors (leaders) involved in transformations of mediumsized cities in Poland and Russia that share similar legacies but took different development paths after the collapse of state socialism. These transformations are discussed using the framework of urban regeneration and are based on empirical data from two cities – Kolomna (Russia) and Kalisz (Poland). The data were obtained through expert interviews, as well as nonparticipant observation in the two cities. Though the process of urban regeneration shows similarities, the process leaders are different.
24 cm
Keywords: transfomacje miast; przemiany miast; odnowa miast; planowanie miejskie; średnie miasta; Europa Wschodnia; Polska; Rosja